2021
DOI: 10.1016/j.pmedr.2021.101456
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in birth Outcomes: A decomposition analysis of contributing factors

Abstract: Highlights Among all factors considered, maternal education contributes the most to racial/ethnic disparities in birth outcomes. Mother’s health insurance coverage significantly helps explain racial/ethnic disparities in birth outcomes. More research is needed to better account for Black-White disparities in birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…to the observed disparities in PTB and LBW between non-Hispanic White and non-Hispanic Black women, followed by health insurance coverage. 65 Southern rural residents, when compared as groups, encounter barriers unique to living in remote regions. They are more likely to be 29,66,67 Low socioeconomic status, limited access, and/or nonavailability of care in Georgia [14][15][16][17]25 may shape lifestyle choices and contribute to chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to the observed disparities in PTB and LBW between non-Hispanic White and non-Hispanic Black women, followed by health insurance coverage. 65 Southern rural residents, when compared as groups, encounter barriers unique to living in remote regions. They are more likely to be 29,66,67 Low socioeconomic status, limited access, and/or nonavailability of care in Georgia [14][15][16][17]25 may shape lifestyle choices and contribute to chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, maternal educational attainment significantly lowered the odds of PTB and LBW, and lack of health insurance increased the odds. Another recent study demonstrated that education can contribute about 10% to the observed disparities in PTB and LBW between non‐Hispanic White and non‐Hispanic Black women, followed by health insurance coverage 65 …”
Section: Discussionmentioning
confidence: 99%
“…Race is a social construct that has been associated with both distance decay and birth outcomes in prior research. 24,25 Metropolitan compared with nonmetropolitan county of residence was defined using the Urban Influence Code developed by the U.S. Department of Agriculture, which differentiates counties based on the population size of the county's metro area or the size and proximity to the nearest metro area. 26 Data were missing on at least one model variable in 49,833 (7.5%) of the birth records.…”
Section: Methodsmentioning
confidence: 99%
“…Racial segregation in Douglas County, Nebraska, continued to exist in 2010, where the Non-Hispanic Black population is still clustered towards the north and the Hispanic/Latino population in the south [20]. Despite growing evidence on the race/ethnic disparities in Douglas County, Nebraska [21], there has been a limited focus on the disparities associated with pediatric asthma. Additionally, the existing literature either focused on the potential role of SDoH on differential environmental exposure or outcomes.…”
Section: Introductionmentioning
confidence: 99%